Pulau Hilang: Wilayah Teritorial Berkurang? - Ersya, Deramadana; Novianti, Novianti (Faculty of Law, Universitas Jambi, 2020)
Global warming becomes as an inevitable issue. This phenomenon has an impact on all aspects of life. One of the impacts is the rise in sea level which can cause the sinking of an island. The study discussed the effect that global warming will have on national borders at the UNCLOS 1982 and that new international policies will be needed to deal with the effects of global warming on country areas. This type of research was normatif yuridis, which sourced in secondary data. By taking several approaches, the approach of legislation (approach approach) and the case approach (case approach). Based on the study, the 1982 sea law convention asa rule in imposing maritime limits has not been able to answer the question of the sea's level rise and impact on the region's capital.